Uji Efek Larvasida Ekstrak Daun Gamal (Gliricida sepium) terhadap Larva Nyamuk Aedes aegypti - Rundito Rundito; Dody Novrial; Eman Sutrisna (Jurnal Surya Medika (JSM), 2022)
Gamal leaves (Gliricidia sepium) well known as liquid organic fertilizer, are also known to have potential as vegetable larvicides because there are flavonoids, triterpenoids, coumarin, coumaric acid, mitotic acid, and stigmastanol glucoside which can be identified and isolated from various parts from Gamal. The aim of this study was to examine the larvicidal effect of Gamal (G. sepium) leaf extract against larvae of Aedes aegypti mosquitoes. The study was conducted using an experimental design with a posttest-only control group design and a completely randomized design consisting of 6 treatment groups. Two groups as control (positive and negative control), while 4 other groups received treatment of Gamal leaf extract (G. sepium) at doses of 50 ppm (P1), 150 ppm (P2), 250 ppm (P3), and 350 ppm (P4). There was no mortality of larvae Aedes aegypti from pure lines after giving Gamal leaf extract, but mortality only occurred in Aedes aegypti larvae positive control group originating from the field. Unknown LC50 and LC90. A total of 13 (52%) Ae. aegypti strain classified as tolerant, while as many as 19 (76%) larvae of Aedes aegypti originating from the field are classified as resistant.